2013
DOI: 10.1038/ncomms3761
|View full text |Cite
|
Sign up to set email alerts
|

Efficient organometal trihalide perovskite planar-heterojunction solar cells on flexible polymer substrates

Abstract: Organometal trihalide perovskite solar cells offer the promise of a low-cost easily manufacturable solar technology, compatible with large-scale low-temperature solution processing. Within 1 year of development, solar-to-electric power-conversion efficiencies have risen to over 15%, and further imminent improvements are expected. Here we show that this technology can be successfully made compatible with electron acceptor and donor materials generally used in organic photovoltaics. We demonstrate that a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
1,337
0
14

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,586 publications
(1,383 citation statements)
references
References 28 publications
32
1,337
0
14
Order By: Relevance
“…They are ideal candidates as efficient ETLs because of their low‐temperature fabrication, suitable energy level alignment, and decent electron mobility 102, 120, 122. Unfortunately, they possess the low electron mobility and photochemical instability 123.…”
Section: Device Structurementioning
confidence: 99%
“…They are ideal candidates as efficient ETLs because of their low‐temperature fabrication, suitable energy level alignment, and decent electron mobility 102, 120, 122. Unfortunately, they possess the low electron mobility and photochemical instability 123.…”
Section: Device Structurementioning
confidence: 99%
“…[21] Organic charge collection layers, such as fullerenes, have been shown to enable highly effective electron extraction when interfaced with the perovskite absorbers [22][23][24] and reduce UV-induced degradation of the solar cell in comparison with devices employing inorganic TiO 2 . [22] The use of organic layers also facilitates fabricating the entire solar cell at low temperatures (no need for the high temperature sintering step required to obtain highly crystalline metal oxide layers), suitable for processing involving temperature sensitive substrates, including flexible plastic foil and for silicon solar cells.…”
Section: Doi: 101002/adma201604186mentioning
confidence: 99%
“…We observe highly efficient quenching of the PL in the steady-state PL spectra of perovskite films coated on C 60 , indicating fast electron transfer from perovskite to C 60 , which is consistent with our previous studies. [23,24] When coating the perovskite films upon 1 wt% N-DPBI doped C 60 films, the PL emission of the perovskite film is even more significantly quenched. For the TRPL decays, we observe a significantly faster PL decay for the films coated upon 1 wt% N-DPBI doped C 60 .…”
Section: Doi: 101002/adma201604186mentioning
confidence: 99%
“…O rganometal trihalide perovskites (OTPs) have recently drawn tremendous research interest as they have demonstrated increased power conversion efficiency (PCE; above 15%) in o5 years of research [1][2][3][4][5][6][7][8][9] . One of the most attractive features of OTP materials is their ability to form very good polycrystals through low-temperature solution processes [10][11][12] .…”
mentioning
confidence: 99%